Trap-TRAP, a Versatile Tool for Tissue-Specific Translatomics in Zebrafish - Corbacho, Jorge; Sanabria-Reinoso, Estefanía; Buono, Lorena; Fernández-Miñan, Ana; Martínez-Morales, Juan R. (Frontiers in Cell and Developmental Biology, 2022)
Developmental and physiological processes depend on the transcriptional and translational activity of heterogeneous cell populations. A main challenge in gene expression studies is dealing with this intrinsic complexity while keeping sequencing efficiency. Translating ribosome affinity purification (TRAP) methods have allowed cell-specific recovery of polyribosome-associated RNAs by genetic tagging of ribosomes in selected cell populations. Here we combined the TRAP approach with adapted enhancer trap methods (trap-TRAP) to systematically generate zebrafish transgenic lines suitable for tissue-specific translatome interrogation. Through the random integration of a GFP-tagged version of the large subunit ribosomal protein L10a (EGFP-Rpl10a), we have generated stable lines driving expression in a variety of tissues, including the retina, skeletal muscle, lateral line primordia, rhombomeres, or jaws. To increase the range of applications, a UAS:TRAP transgenic line compatible with available Gal4 lines was also generated and tested. The resulting collection of lines and applications constitutes a resource for the zebrafish community in developmental genetics, organ physiology and disease modelling.